Análise do processo de implantação das compras públicas sustentáveis da Universidade Federal do Ceará fundamentado em um modelo de compras públicas sugerido pelo Governo Federal Brasileiro - Ferreira, Thayanne Alves (2014)
The volume of purchases made by public companies is significant. It is necessary that the procurement process is developed aiming a balance between what purchases and conservation of the planet's resources. The aim of this study is to examine the deployment process of public sustainable procurement of the Federal University of Ceará based on a methodology of public purchases suggested by the federal government. The purpose of the research can be classified as applied, and the goals can be determined asexploratory and descriptive. Qualitat ive and quantitative approach was used in the development of research. The exploratory qualitative phase was conducted through semi - structured interviews with the staff that participate in the buying process of the university. Content analysis techniques w ere used on the information gathered. In the quantitative phase, a structured questionnaire was used with staff that was responsible for strategic sectors of the Dean of University Administration. To compare the process that the university has been develop ing with existing models, a methodology developed by ICLEI - LACS (Local Governments for Sustainability), which is an international association formed by local governments and other government organizations was used. The method of implementation of public su stainable procurement was developed based on the flexibility, being applicable to any public authority. The methodology consists of five steps: planning; definition of goals and objectives; construction of the action plan; implementing the plan and monitor ing of results. The main findings show that there is not yet a policy of using sustainability criteria in the purchasing process of the organization. Due to charges of inspection organs and provisional measures, a sustainable logistics plan that brings var ious aspects related to sustainability, including, purchasing and bidding has been created. A sustainable schedule and a actions were drawn in the plan. The public sustainable presents the change in patterns of purchases of goods and services from federal institutions, requiring transformation in purchasing practices, to become an instrument for achieving the objectives of sustainable development